Perlindungan Hukum terhadap Hak Privasi dan Rekam Medis Pasien pada Masa Pandemi Covid-19 - Kastania Lintang; Yeni Triana (Jurnal Hukum Lex Generalis, 2021)
Health development is one of the national goals of the Indonesian nation based on the Preamble to the 1945 Constitution of the Republic of Indonesia. After the enactment of the 1945 Constitution of the Republic of Indonesia, the discussion of the right to health is re-regulated in Article 28H paragraph (1). Regulations regarding patient rights are listed in Law no. 36 of 2009 concerning Health, Law no. 29 of 2004 concerning Medical Practice, and Law no. 44 of 2009 concerning the Hospital. However, patients' rights cannot be fully implemented during the COVID-19 pandemic. So, the author will discuss how the legal protection of the right to privacy and medical records during the COVID-19 pandemic. This research is normative legal research. The conclusion of this research is that in an emergency condition, guaranteeing that the fulfillment of patient rights categorized as derogable rights is a right that can be limited or postponed.